ADVANTAGES OF ASSESSMENT INDICATORS OF FINANCIAL STATEMENTS OF JOINT VENTURES (World Economics and Finance Bulletin, 2023)
The article describes the procedure for evaluating profitability, efficiency, liquidity, and financial stability indicators by analyzing financial reports of joint ventures.